2019
DOI: 10.3892/ol.2019.10483
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‑associated macrophages affect the biological behavior of lung adenocarcinoma A549 cells through the PI3K/AKT signaling pathway

Abstract: Tumor associated macrophages (TAMs) are a major type of inflammatory cell in a tumor microenvironment. Previous evidence has suggested that TAMs promote tumorigenesis, growth, invasion and metastasis, thereby affecting tumor metabolism. The mechanisms through which they affect the invasion and metastasis of lung cancer cells remain unclear. The present study investigated the effects and molecular mechanisms of TAMs on the proliferation, invasion and migration of lung adenocarcinoma A549 cells. Human mononuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Numerous studies confirmed that in lung cancer TAMs contribute to tumor progression and metastasis through the production of variety of chemokines and growth factors (156,(161)(162)(163). In vitro lung carcinoma cells (human NSCLC A549 cells) induce polarization of THP-1 cells to CD206+ M2 phenotype (156).…”
Section: Tams In Lung Tumors and Metastasismentioning
confidence: 94%
“…Numerous studies confirmed that in lung cancer TAMs contribute to tumor progression and metastasis through the production of variety of chemokines and growth factors (156,(161)(162)(163). In vitro lung carcinoma cells (human NSCLC A549 cells) induce polarization of THP-1 cells to CD206+ M2 phenotype (156).…”
Section: Tams In Lung Tumors and Metastasismentioning
confidence: 94%
“…M2 macrophages are tumor-supportive cells and are characterized by high levels of IL-10, CC-chemokine ligand 18 (CCL18), CC-chemokine ligand 22 (CCL22), and matrix metalloproteinase 9 (MMP9) [24,25]. And M2 macrophages bear a striking resemblance to TAMs [26], which is an important component of tumor immune microenvironment [27,28]. In addition to chemical inducers, matrix stiffness also participates in inducing THP-1 cell polarization [29].…”
Section: Introductionmentioning
confidence: 99%
“…In co-culture assays, 1 × 10 5 human monocytic THP-1 cells (ATCC ® ), seeded in RPMI-1640 medium containing 10% FBS, were stimulated with 500 nM phorbol-12 myristate 13-acetate (PMA) for 24 h in order to favor their differentiation into macrophages [25]. Floating THP-1 cells were removed by washing the dishes twice with PBS; attached cells-i.e., macrophage-differentiated cells-were rinsed with fresh medium.…”
Section: Co-culture Modelsmentioning
confidence: 99%